Paving the path: drivers of standardization participation at ISO - Knut Blind; Maximilian von Laer (The Journal of Technology Transfer, 2021)
Several studies investigating the trade effects of standardization have found a positive impact of the number of international standards in a country on its trade volumes. While international standards have so far been considered as exogenous, we investigate what drives countries to take over leading roles, i.e. secretariats, in committees of the International Organization for Standardization (ISO) using a panel dataset on the ISO participation of 12~countries. Looking at this phenomenon through the perspective of agenda setting in international institutions we expect ISO participation to be a desirable tool for shaping technological trajectories and substantiating global influence via international technology transfer. We find that, while for most countries no systematic pattern can be observed, both China and the US show a close correlation between R&D and standardization work at ISO. For China, we attribute this finding to having a strategic approach toward standardization participation, for the US to the distinct features of the decentralized US standardization system. Finally, we derive implications of findings for both research and practice.
Keywords: 600; Standardization; International technology transfer; Research; Trade